2015
DOI: 10.1111/aogs.12654
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomies in Finland in 1990–2012: comparison of outcomes between trainees and specialists

Abstract: Laparoscopic hysterectomy is more common in Finland than in the other Nordic countries. Although trainees need more time to operate, there were no differences between the trainees and the specialists with regard to major complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
1
12
0
2
Order By: Relevance
“…5 However, when comparing procedures performed by trainees or specialists, the rate of major complications requiring reoperation remained the same. 11 The use of laser angiography during robotic hysterectomy to assess the perfusion of the vaginal cuff and guide intraoperative decisions has been assessed in a feasibility trial including 20 women recently with good results. 12 Vaginal atrophy, co-morbidities that influence the healing process, increased age, smoking, radiation treatment, hysterectomy due to malignancy and infection have also been reported as risk factors for VCD.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, when comparing procedures performed by trainees or specialists, the rate of major complications requiring reoperation remained the same. 11 The use of laser angiography during robotic hysterectomy to assess the perfusion of the vaginal cuff and guide intraoperative decisions has been assessed in a feasibility trial including 20 women recently with good results. 12 Vaginal atrophy, co-morbidities that influence the healing process, increased age, smoking, radiation treatment, hysterectomy due to malignancy and infection have also been reported as risk factors for VCD.…”
Section: Discussionmentioning
confidence: 99%
“…Når nye operasjonsmetoder innføres ved et sykehus, er kvalitetskontroll av metoden viktig. I andre nordiske land finnes hysterektomiregistre hvor operasjonsmetoder og resultater fortløpende registreres (3,7,8). Norge har ikke et slikt landsdekkende register.…”
Section: Fortolkningunclassified
“…Tendensen til å velge mindre invasive operasjonsmetoder gjenfinnes også i andre studier (3,6,9,10). Generelt anbefales vaginal hysterektomi dersom dette er mulig (11)(12)(13).…”
Section: Materiale Og Metodeunclassified
“…The surgeon's experience has been found to be important in reducing severe complications, especially in laparoscopic and vaginal hysterectomies. 5 However, no difference in major complications requiring reoperation was found between trainees and specialists in a later study 18. Nevertheless, a recent study reported that in centers with high laparoscopic expertise, the incidence of vaginal dehiscence is significantly lower when the entire procedure is completed laparoscopically compared with vaginal suturing of the cuff after TLH 17.…”
mentioning
confidence: 94%